Examining the role of patient-reported external factors and risk of relapse in anti-neutrophilic cytoplasmic autoantibody vasculitis - Collie, Mary M.; Chen, Dhruti P.; Hu, Yichun; Blazek, Lauren N.; Derebail, Vimal K.; Wu, Eveline Y.; Jain, Koyal; Orzechowski, Nicole; Poulton, Caroline J.; Henderson, Candace D.; Falk, Ronald J.; Hogan, Susan L. (Frontiers in Nephrology, 2024)
The role of stressors, insect bites, and infections on disease relapse of ANCA vasculitis has yet to be entirely explored, with limited retrospective studies focused on disease onset from small participant cohorts. Our study analyzes longitudinal survey data from 2011–2022 to evaluate this perspective from a large ANCA vasculitis cohort. We collected surveys every three to six months to obtain information on self-reported psychological stressors and significant life events, insect bites, and infections throughout clinical disease. We defined cohorts as those who relapsed (Relapse Cohort) and controls as those who did not relapse (Remission Cohort) during the study period. Survey responses were retrospectively reviewed during a 15-month timeframe prior to relapse or during 15 months of remission and categorized by type of stress event, insect bite, and infections at every available 3-month interval. There were no significant differences in stress and insect bites between the relapse and remission cohorts. Patients who relapsed reported more frequent upper respiratory infections and other infections, such as those affecting the skin and eyes, but there were no significant differences in the incidence of pulmonary or urinary infections compared to the remission cohort. There was a significant difference in reported upper respiratory infections 9 to 15 months prior to the relapse date, indicating a remote history of infections as a potentially significant physical stressor that may contribute to disease relapse. More frequent patient-reported infections, specifically upper respiratory infections, may contribute to patient vulnerability to relapse. Counseling and close monitoring of patients after infectious symptoms could aid in earlier detection of disease flares. Future studies are essential to further understand the importance of distal risk factors and how they impact relapse.